A Simple, Artistic and Efficient Modification of the Inversion Method - Ram Prakash; Krishna Prakash (Mashhad University of Medical Sciences, 2018)
The simplest and fastest way of producing an acceptable and accurate cast is by adopting the two-pour or inversion method. This process is slightly cumbersome and messy due to difficulty of access. A much more efficient, easy and artistic way of accomplishing it is described by adopting a Rotating Cake Icing Table with a Silicone Baking Mat on top as an autoclavable non-stick barrier.